(untitled) (Ameghiniana, 2025)
The world’s record of ichthyosaurs and plesiosaurs from the Aalenian–Bathonian interval (Middle Jurassic) is very scarce, and their presence in the Neuquén Basin is particularly significant for understanding the evolutionary history of these marine reptiles during the Jurassic. At Chacaico Sur (southwestern Neuquén), the Los Molles Formation yields a unique record of these animals, accounting for the presence of Maresaurus coccai, Chacaicosaurus cayi, and Mollesaurus periallus. The age assigned to this unit in the mentioned area is early Bajocian, based on microfossils and macroinvertebrates. We studied the calcareous nannofossils to contribute to the age constraint and paleoenvironmental reconstruction. The recovered assemblage is composed of Carinolithus magharensis, Carinolithus superbus, Cyclagelosphaera margerelii, Discorhabdus striatus, Retecapsa incompta, Watznaueria britannica, Watznaueria contracta, Watznaueria manivitiae, Watznaueria sp. indet., and Schizosphaerella punctulata. This assemblage presents typical Bajocian features in the Neuquén Basin: low abundance and diversity, and dominance of W. britannica. Overall, this assemblage would indicate an early Bajocian age, Subzone NJT10a, based on the co-occurrence of C. superbus and W. manivitiae. The low diversity and abundance might indicate shallow marine conditions related to the onset of a regressive phase in the basin. These results provide a new temporal and paleoenvironmental context for understanding the evolutionary history and ecology of Mesozoic marine reptiles.